Cysteine as a Multifaceted Player in Kidney, the Cysteine-Related Thiolome and Its Implications for Precision Medicine - Correia, Maria João (2022)
Funding Information: This research was supported by Fundação para a Ciência e Tecnologia (PTDC/MED-TOX/30418/2017) and iNOVA4Health (UID/Multi/04462/2013). M.J.C., D.G.F.F. and J.M. were supported by FCT (PhD grant SFRH/BD/131331/2017, PhD grant PD/BD/135484/2018 and postdoctoral contract PTDC/MED-TOX/30418/2017, respectively).